Software Engineering and Formal Methods 10th International Conference, SEFM 2012, Thessaloniki, Greece, October 1-5, 2012. Proceedings - Eleftherakis, George; Hinchey, Mike.; Holcombe, Mike.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 10th International Conference on Software Engineering and Formal Methods, SEFM 2012, held in Thessaloniki, Greece, in October 2012. The 19 revised research papers presented together with 3 short papers, 2 tool papers, and 2 invited talks were carefully reviewed and selected from 98 full submissions. The SEFM conference aspires to advance the state-of-the-art in formal methods, to enhance their scalability and usability with regards to their application in the software industry and to promote their integration with practical engineering methods.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Artificial intelligence; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages; Computer Communication Networks; Artificial Intelligence (incl. Robotics).